1998
DOI: 10.1098/rspb.1998.0516
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of mating, egg production and death rates in females of the Mediterranean fruitfly, Ceratitis capitata

Abstract: Costs of reproduction include costs of producing eggs and of mating itself. In the present study, we made an experimental investigation of costs of reproduction in the Mediterranean fruit fly (medfly, Ceratitis capitata). We demonstrated that virgins live longer than non-virgin females. However, in strong contrast to most findings within the Diptera, non-virginity had no detectable effect on egg production. Therefore the increased longevity of the virgin females cannot be attributed to an increase in egg produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
190
3
9

Year Published

2000
2000
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 215 publications
(209 citation statements)
references
References 111 publications
(77 reference statements)
7
190
3
9
Order By: Relevance
“…Although we did not compare defined and conventional diets directly, median lifespans of 68-75 days for flies fed the defined diets were 36-50% longer than expected for flies fed conventional diets, and maximum lifespans of 84-91 days for flies fed the defined diets were 12-21% longer than expected for flies fed conventional diets, regardless of methionine or sugar concentration. This observed longevity is particularly impressive because non-virgin females of the present study would be expected to have shorter lifespans than those reported previously for virgin females, due to the cost of reproduction (Chapman et al 1998). The full impact of these defined media on longevity in relation to fecundity in both female and males remains to be explored (Good and Tatar 2001;Magwere et al 2004).…”
Section: Discussionmentioning
confidence: 61%
“…Although we did not compare defined and conventional diets directly, median lifespans of 68-75 days for flies fed the defined diets were 36-50% longer than expected for flies fed conventional diets, and maximum lifespans of 84-91 days for flies fed the defined diets were 12-21% longer than expected for flies fed conventional diets, regardless of methionine or sugar concentration. This observed longevity is particularly impressive because non-virgin females of the present study would be expected to have shorter lifespans than those reported previously for virgin females, due to the cost of reproduction (Chapman et al 1998). The full impact of these defined media on longevity in relation to fecundity in both female and males remains to be explored (Good and Tatar 2001;Magwere et al 2004).…”
Section: Discussionmentioning
confidence: 61%
“…Malederived substances which affect female receptivity are common in insects (see e.g. Chapman et al 1998;Wedell 2005 for examples in Diptera and Lepidoptera). Thus, there is the possibility that, disguised in nuptial gifts, males may transfer substances, which regulate female remating behaviour (see also Leopold 1976;Chen 1984).…”
Section: Discussionmentioning
confidence: 99%
“…Parker 1979; Arnqvist and Rowe 2005) over female remating behaviour will be generated, as male adaptations will be favoured that enforce or extend female refractory period in order to avoid sperm competition Simmons and Gwynne 1991;Stockley 1997). Chemicals transferred at mating that increase the refractory period of females have frequently been reported (see Leopold 1976;Chen 1984;Chapman et al 1998). In their theoretical analysis on male and female interests concerning nuptial feeding in insects, Parker and Simmons (1989) therefore interpreted these substances as a means by which males could manipulate female reproduction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, sperm replenishment may influence female reproductive output (e.g. Baker et al , 2001;Drnevich et al , 2001 ) and substances in the ejaculate may induce egg production (see, for example, Chapman et al , 1998 ) and stimulate oviposition ( Leopold, 1976;Eberhard, 1996 ). Therefore, in many studies demonstrating direct benefits from nuptial gifts ( Hayashi, 1998;Ryne et al , 2001;Fedorka & Mousseau, 2002;Rooney & Lewis, 2002 ; for earlier papers see Vahed, 1998 ) it is difficult to disentangle benefits from nuptial feeding from other effects resulting from multiple mating or increased sperm transfer (but see Gwynne, 1984;Steele, 1986;Simmons, 1988Simmons, , 1990Brown, 1997;Reinhold, 1999 ).…”
Section: Introductionmentioning
confidence: 99%